If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 55 = 11x + 94 Reorder the terms: 55 + 14x = 11x + 94 Reorder the terms: 55 + 14x = 94 + 11x Solving 55 + 14x = 94 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 55 + 14x + -11x = 94 + 11x + -11x Combine like terms: 14x + -11x = 3x 55 + 3x = 94 + 11x + -11x Combine like terms: 11x + -11x = 0 55 + 3x = 94 + 0 55 + 3x = 94 Add '-55' to each side of the equation. 55 + -55 + 3x = 94 + -55 Combine like terms: 55 + -55 = 0 0 + 3x = 94 + -55 3x = 94 + -55 Combine like terms: 94 + -55 = 39 3x = 39 Divide each side by '3'. x = 13 Simplifying x = 13
| 7x-4(x-3)=33 | | t/250=150/375 | | 1/4(2x+5)=x-2/5 | | =(7x+9y-2x)(8x-3x-3y) | | 7x+1=2x+6 | | 1/2+(0.7)2 | | (3x+2)=(x-7) | | -9x+63=135 | | (m^-1m5/m^-2)^-3 | | -1/12x+8=7/6 | | x/0.02=32.8 | | -3x=18.9 | | 4c-6=250 | | 47y+5x=360 | | 3x-10=12x | | x(3x^2+5x-4)-3(3x^2-x)=0 | | X*X-3=-2 | | 7(r+3)= | | 2x+7y=28 | | 8p+4-8p= | | x*.06=3500 | | 6x-73+8x+43=180 | | 5t+36=-249 | | x/-8=-5 | | -4m+5.5=16 | | x/7-56=-54 | | y2=25/49 | | 4x-37=-13 | | 2x+114+8x+72=180 | | 6x+8=-33-8x | | 4x+3=-8x-21 | | (X+3)(x-2)=4(x+1) |